Sexual and reproductive health concerns of adolescents living with perinatally infected HIV in India - Mysore Narasimha Vranda; Doddaballapura K Subbakrishna; Jayashreee Ramakrishna; Hukunda Gundaiah Veena (Indian Journal of Community Medicine, 2018)
Background: With improved access to highly active antiretrieval treatment, many children with perintally acquired HIV are now able live longer. These children are now reaching into adolescence and sexually active. This qualitative, explorative study examines the sexual and reproductive health (SRH) needs and concerns of adolescents living with HIV (ALHIV) in India. Materials and Methods: We used qualitative research design to collect the data. Twenty participants were recruited from two nongovernmental organizations which provide shelter care, education, and emotional and social support to HIV/AIDS orphan children located in Bengaluru District of Karnataka State using purposive sampling. In-depth interview guide was prepared and used to elicit the adolescents' concerns, knowledge, and perspective related to sexuality, marriage, child bearing, and barriers in availing SRH services in the context of HIV. Results: Totally, four themes were emerged from that qualitative data based on thematic analysis, which are as follows: “Perceived challenges in relation to romantic relationship;” “Confusion regarding whether to marry person with HIV positive or HIV negative;” “Aspiration to have children,” and “Perspective of ALHIV in relation to SRH needs and concerns.” Conclusion: The findings of the research brought out the need for policies and guidelines specifically targeting the SRH needs and concerns of ALHIV.